Good Debt or Bad Debt? - Roberto Tamborini (CESifo GmbH, 2024)
The public debt overhang spread across advanced countries, and the reform of the Stability and Growth Pact in the Euro Zone, have revived the polarization between those who think that debt is always good and those who think that debt is always bad. This paper presents a normative model of endogenous growth with debt-financed public capital. It is shown that no meaningful assessment of debt and its effect on growth and sustainability at any point in time is possible without reference to the whole debt trajectory and the specific state of the economy along the trajectory. An orderly and consistent analysis may be developed along two coordinates of debt: sustainability/unsustainability, and efficiency/inefficiency. "High" and "low" debt/GDP ratios may equally be efficient and sustainable. On the other hand, debt may be sustainable but inefficient (sub-optimal growth), or sustainable and efficient ex-ante but unsustainable ex-post, or inefficient and unsustainable.
Keywords: E62; H63; O40; 330; public debt; debt burden; debt sustainability; economic growth; endogenous growth models